2014
DOI: 10.5539/gjhs.v7n2p228
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Quality of Work Life and Job Satisfaction of Faculty Members in Zahedan University of Medical Sciences

Abstract: Background:Quality of work life is one of the most important factors for human motivating and improving of job satisfaction.Aim:The current study was carried out aimed to determine the relationship between quality of work life and job satisfaction in faculty members of Zahedan University of Medical Sciences.Method:In this descriptive-analytic study, 202 faculty members of Zahedan University of Medical Sciences in 2012 were entered the study through census. The job satisfaction questionnaire of Smith and Kendal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 8 publications
(13 reference statements)
5
23
0
3
Order By: Relevance
“…In fact, the results showed that there is a need to improve the QWL and increase JS in Ahvaz health centers. These results were consistent with those of the previous studies (19)(20)(21)(22).…”
Section: Discussionsupporting
confidence: 94%
“…In fact, the results showed that there is a need to improve the QWL and increase JS in Ahvaz health centers. These results were consistent with those of the previous studies (19)(20)(21)(22).…”
Section: Discussionsupporting
confidence: 94%
“…), determinants of the growth, decline and competitiveness of organisations [61]; and (ii) as a set of non-economic factors, as a subject of research in the quality of academic life of students (QAL) (satisfaction with services, emotions felt in campus, etc. ), e.g., [62][63][64][65][66][67][68], or as a factor for assessing quality of work life (needs for satisfaction in a physical and emotional line) (QWL) [69][70][71][72][73].…”
Section: Sustainable Development Practices and Quality Of Lifementioning
confidence: 99%
“…However, the present study focuses specifically on HEIs, using the definition proposed in [85] for conceptualizing QWL-that is, the staff's satisfaction with a variety of needs through resources, activities and results arising from participation in the workplace; and for measures of QWL, the updated needs proposed by the first authors were stated in [86]. Various studies in the field of QWL dealt with HEI teachers/researchers [70,71,73], but so far no studies are known to have dealt with the relationship between sustainable development practices in HEIs and the QWL of teachers/researchers, and so this is an innovative approach with potential interest for both researchers and HEI managers.…”
Section: Sustainable Development Practices and Quality Of Lifementioning
confidence: 99%
“…Quality of Work Life merupakan salah satu faktor penting untuk motivasi manusia dan meningkatkan kepuasan kerja (Kermansaravi et al, 2015). Quality of Work Life (kualitas kehidupan kerja) adalah konsep yang komprehensif yang terdiri dari kesehatan fisik dan psikologis, situasi ekonomi, kepercayaan pribadi dan interaksi dengan lingkungan (Khorsandi et al, 2010).…”
Section: Pendahuluanunclassified